The European Union's response to the trade crisis - Uri Dadush; Guntram B. Wolff (Bruegel, 2019)
The global trading system, a source of prosperity, is under attack on various fronts. The causes run deep and require a strategic response from the European Union and from the main trading nations. The future of the system hinges on the answer to three questions, and the scenarios associated with them: - Can the World Trade Organisation be reformed? - Is the United States' scepticism about the system a new normal? - Can China undertake reforms that would make its system more compatible with the WTO? The possible outcomes for the global trading system could be good or bad, depending on how each of these issues is resolved. Under a good set of scenarios, the EU should persist on its current course with some significant adjustments. We call this Plan A, which would aim to preserve the multilateral trading system. Under a bad set of scenarios, the EU will have to contend with a possible break-up of the multilateral trading system, requiring the formulation of a Plan B. The EU needs today to put in place its Plan B, not only to prepare for a far less favourable trading environment, but also to clarify the trade-offs implicit under Plan A. All major trading nations must recognise that the alternative to making compromises is not the status quo, but something much worse.
Keywords: 330